PHYSICAL-AND-CHEMICAL FEATURES AND MECHANISM OF COPPER OXIDE (I) FORMATION IN ALKALINE CHLORIDE SOLUTIONS - Dospaev M.M.; Bayeshov A.; Dzhilkibayeva M.O.; Zhumakanova A.S.; Dospaev D.M.; Kakenov K.S.; Esenbaeva G.A. (Academic Scientific Journal of Chemistry, 2019)
The most promising ways to obtain highly dispersed copper oxides are electrochemical methods. This method of transferring copper into a solution allows finding accurately the formation modes of the required valence ion and obtaining high chemical purity compounds. The methods of producing copper oxide (I) are based on the anodic oxidation of metallic copper in an alkaline chloride-containing solution. The main advantage of the electrochemical method is the possibility of obtaining high quality powder with a smaller particle size not containing metallic copper and bivalent copper oxide. The results of studying anodic corrosion of copper in weakly alkaline and acidic chloride solutions show that, depending on the content of chloride ions in the solution and the specified potential value, there can be formed complex copper chloride compounds that in the process of hydrolysis form copper oxide (I) powder. The region of thermodynamically stable existing of monovalent copper chloride complexes at low potential values and pH increases. In this work there has been for the first time made the calculation and a diagram has been constructed that allows determining only the most probable pH, pCl– and the electrode region, in which copper oxide (I) can be obtained.